‘Ikhwān al-Ṣafā’ wa Falsafatuhum al-Siyāsīyya - Zamzam Afandi (Al-Jami'ah: Journal of Islamic Studies, 1997)
Ikhwan as-Safa, a group of philosophers which rised in 4th century of Higra or l0th century AD, in Basra, Irak, has attracted many scholars to study their thought, especially their scientific ideas which were compiled on their master piece Rasa'il lkhwan as-Safa wa Khulan al-wafa. This paper tries to raise their notion on political philosophy in regard to the assumption that Ikhwan as-Safa was not merely a group of philosophers whose concerns were purely scientific matters, but also a group of philosophers with political concerns. They dreamt of an idealistic country which they called al-Madina al-Fadilah as a substitute of an evil country, a country filled with evils, corruptions a deviation which they called al-Madina al-Ja'ira. In order to know further their idealistic country, one should understand their concepts of human being, country, leadership and how to choose the leader. These points are discussed here. According to Ikhwan, human being is a social creature. They cannot live alone and autonomous in doing such aspects as trade, industry, science and so forth. For them social life for them is a kind of obligatory, for two reasons. The first is because human being cannot autonomously discover their potentials, whether in scientific aspects or in other aspects of life. The second is the different ability of every single person as well as their natural potentials. This condition leads them to a position in which they cannot master all sciences and skills. Umma or society, according to Ikftwan, is a nation with similarities in language, characteristics, traditions, culture, geography, as well as color of skin and physical posture. The idealistic country for them is a country whose society consist of good people ‘Qaumun akhyarun', philosophers or wise people, and it has rules of social relation among themselves or between them and People of evil country. These criteria must be based on obedience to Allah. Dealing with imama or leadership, Ikhwan sees it as obligatory. Imama should exist, not only for mundane aspects resolving conflict, but also for religious goals. For them a leader (imam) must have their criteria mentioned earlier.